2010
DOI: 10.1111/j.1365-3040.2010.02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligands of boron in Pisum sativum nodules are involved in regulation of oxygen concentration and rhizobial infection

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
(113 reference statements)
6
14
0
Order By: Relevance
“…However, as mentioned earlier, symptoms of B deficiency appeared in nodules earlier than in shoots or roots (Bolaños et al. , 1994), and B deficiency apparently did not elicit ROS production and oxidative damage in nodules (Reguera et al. , 2010c).…”
Section: Main Effects Of Boron (B) Deficiency (–B) and The Supplemenmentioning
confidence: 78%
See 1 more Smart Citation
“…However, as mentioned earlier, symptoms of B deficiency appeared in nodules earlier than in shoots or roots (Bolaños et al. , 1994), and B deficiency apparently did not elicit ROS production and oxidative damage in nodules (Reguera et al. , 2010c).…”
Section: Main Effects Of Boron (B) Deficiency (–B) and The Supplemenmentioning
confidence: 78%
“…Genes typically involved in nodulation were either up‐regulated (including several early and late nodulins) or down‐regulated, for example, leg‐haemoglobin genes previously reported in B‐deficient Pisum sativum nodules (Reguera et al. , 2010c).…”
Section: Main Effects Of Boron (B) Deficiency (–B) and The Supplemenmentioning
confidence: 98%
“…Furthermore, B is needed for the signalling of plant-derived glycoproteins for bacteroid differentiation into the N 2 -fixing form (Bolaños et al, 2001). Recently, Reguera et al (2010) concluded that B helps to stabilise nodule macromolecules that are important for rhizobial formation and for regulation of oxygen concentration in nodules of Pisum sativum. In Frankia symbiosis, the known role of B is in the stability of the envelopes that prevent access of oxygen to the N 2 -fixing vesicles (Bolaños et al, 2002).…”
Section: Boron and Root Nodulesmentioning
confidence: 98%
“…(Table 1). Apart from this, the bioavailability of boron is also necessary for nitrogen fixation and nitrate assimilation (Camacho-Cristóbal and González-Fontes 1999;Matas et al 2009;Reguera et al 2010;Beato et al 2010), for oxidative stress (Pfeffer et al 1998;Kobayashi et al 2004) and root development (Dugger 1973;Martín-Rejano et al 2011). However, its presence beyond the permissible limit hampers plant growth and crop productivity worldwide (Stangoulis and Reid 2002;Reid et al 2004).…”
Section: Boron (B)mentioning
confidence: 99%